Determining the influence of thermomechanical loading on the measurement errors of fiber-optic gyroscope - Breslavsky, Dmytro; Uspenskyi, Valerii; Mietielov, Volodymyr; Senko, Alyona; Tatarinova, Oksana (Technology center PC, 2025)
The object of this study is the measurement errors of a fiber-optic gyroscope, which is an element of the spacecraft orientation control system. The task to determine the patterns of thermomechanical loading influence on the measurement errors of gyroscopes has been solved by using mathematical modeling. The study was conducted using the finite element method, which has made it possible to analyze the stress-strain state of structural elements under different conditions of temperature and mechanical loading. Temperature and deformation distributions of the spacecraft structural elements were obtained. These data were used to estimate the misalignment parameters of the sensitivity axes of the onboard system gyroscopes, which arise due to structural deformation. Under certain modeling conditions, they exceed one hundred arc seconds, which could lead to an unacceptable error in controlling the spacecraft orientation. To specify the magnitude of gyroscopes’ measurement error, high-frequency oscillations that occur when the jet engine is turned on during the correction of the spacecraft's orbit were considered together with thermal deformation of the structure. This combination of thermal and mechanical effects creates conditions under which the accuracy of the control systems is significantly compromised. It was determined that under the conditions studied, the measurement error increases 8 times when the temperature of the structure changes by 40 °C. Thus, to solve the task set, a procedure for determining the measurement error under specific conditions of thermomechanical loading was devised and described. Using such a procedure in the design of control systems in the future will contribute to increasing the accuracy of their operation. This will be achieved by optimally placing gyroscopes on board, taking into account the influence of thermal fields.
Keywords: thermomechanical deformation; finite element method; misalignment of a fiber-optic gyroscope; measurement errors